Mechanisms of Inflammation Chronification: Gene and Epigenetic Regulation of Intolerant Response (Trained Immunity) - Orekhov, Alexander Nikolaevich; Omelchenko, Andrey Vladimirovich; Zhuravlev, Alexander Dmitrievich; Vinokurov, Andrey Yurievich; Elizova, Natalia Vladimirovna; Sinyov, Vasily Vladimirovich; Sobenin, Igor Alexandrovich; Sukhorukov, Vasily Nikolaevich (Current Medicinal Chemistry, 2026)
AimsThis study aims to elucidate the mechanisms contributing to the transition from acute to chronic inflammation, particularly in the context of atherosclerosis, by investigating the pro-inflammatory responses of cybrid cell lines derived from patients with coronary heart disease.BackgroundAcute inflammatory reactions are essential components of the innate immune response, typically resolving within hours or days. However, disruptions in this process can lead to chronic inflammation, which is linked to significant morbidity and mortality. Atherosclerosis, characterized by chronic vascular inflammation, poses a major health threat, underscoring the need for understanding its underlying mechanisms.ObjectivesThe primary objective is to analyze the pro-inflammatory cytokine responses of 14 cellular lines, including 13 cybrids and one maternal line (THP-1), to identify intolerant and tolerant responses to key cytokines associated with inflammation.MethodsWe utilized cybrid cell lines created by fusing THP-1 monocytic cells with platelets from patients diagnosed with atherosclerosis. Cytokine responses were assessed through quantitative analysis of IL-1β, IL-6, MPC-1, IL-8, and TNF-α secretion. Gene expression profiles were analyzed to correlate cytokine secretion with specific gene regulation patterns, focusing on epigenetic mechanisms influencing immune responses.ResultsDistinct intolerant and tolerant responses were observed across the cellular lines for key cytokines. Specifically, TC-HSMAM1 and TCP-521 were intolerant to IL-1β, TC-HSMAM1, TC-LSM2, and TC-522 were intolerant to IL-6, six lines exhibited intolerance to MPC-1, and eight lines were intolerant to IL-8. No intolerant responses were noted for TNF-α. Gene expression analysis revealed that at least ten genes correlated with increased cytokine secretion in intolerant reactions, while 23 genes showed higher expression during these intolerant responses, indicating significant roles for DNA modification and chromatin remodeling. An important finding emerged from the study of agents affecting histone modification. Specifically, unlike other agents, sodium butyrate not only exhibited a stronger suppression of the inflammatory response in cells but also eliminated their intolerance to inflammatory stimulation. Therefore, in the near future, sodium butyrate could be regarded as a fundamentally new anti-inflammatory preventive and therapeutic agent, with its mechanism of action rooted in the prevention and suppression of chronic inflammation.DiscussionIn chronic non-infectious diseases like atherosclerosis the intolerant response or trained immunity can worsen inflammation. This study shows that both genetic and epigenetic regulation contribute to this intolerant response. It was also found that sodium butyrate can prevent the intolerant response, suggesting it may become a new anti-inflammatory agent that suppresses chronic inflammation.ConclusionOur findings have suggested that the interplay between pro-inflammatory cytokine responses and epigenetic regulation mechanisms is critical in determining whether a cell exhibits a normal or intolerant immune response. Understanding these dynamics may provide insights into the chronic inflammatory processes associated with atherosclerosis and other related conditions.
Keywords: cybrid